Exploring the role of COVID-19 pandemic-related changes in social interactions on preschoolers' emotion labeling - Wermelinger, Stephanie; Moersdorf, Lea; Ammann, Simona; Daum, Moritz M. (Frontiers in Psychology, 2022)
During the COVID-19 pandemic people were increasingly obliged to wear facial masks and to reduce the number of people they met in person. In this study, we asked how these changes in social interactions are associated with young children’s emotional development, specifically their emotion recognition via the labelling of emotions. Preschoolers labelled emotional facial expressions of adults (Adult Faces Task) and children (Child Faces Task) in fully visible faces. In addition, we assessed children’s COVID-19-related experiences (i.e., time spent with people wearing masks, number of contacts without masks) and recorded children’s gaze behaviour during emotion labelling. We compared different samples of preschoolers (4.00 to 5.75 years): The data for the no-COVID-19-experience sample were taken from studies conducted before the pandemic (Adult Faces Task: Widen & Russell, 2010; N = 40; Child Faces Task: Streubel et al., 2020; N = 30). The data for the with-COVID-19-experience sample (N = 99) were collected during the COVID-19 pandemic in (country, blinded for review) between June and November 2021. The results did not indicate differences in children’s labelling behaviour between the two samples except for fearful adult faces. Children with COVID-19-experience more often labelled fearful faces correctly compared to children with no COVID-19 experience. Furthermore, we found no relations between children’s labelling behaviour, their individual COVID-19-related experiences, and their gaze behaviour. These results suggest that, even though the children had experienced differences in the amount and variability of facial input due to the pandemic, they still received enough input from visible faces to be able to recognise and label different emotions.